The Oxford Handbook of Music Education, Volume 1 2012
DOI: 10.1093/oxfordhb/9780199730810.013.0036_update_001
|View full text |Cite
|
Sign up to set email alerts
|

The Young Singer

Abstract: Development of the singing voice is especially important for the young. Those who learn to sing early reap a lifetime of benefits, which, in addition to developing aesthetic awareness, include personal, social, and educational outcomes. Singing is a skill that requires disciplined study if the singer is to develop his/her potential. While vocal music teachers agree that children can and should learn to sing, some have considered it inappropriate to teach singing to children via formal instruction. Fortunately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Increases in range, vocal stability, and tone quality were among the most frequently described voice changes; however, decreases in the same areas were also reported. These findings support those of earlier descriptions of FAVC (Gackle, 2019; Huff-Gackle, 1985; Monks, 2003; Phillips et al, 2012; Williams et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Increases in range, vocal stability, and tone quality were among the most frequently described voice changes; however, decreases in the same areas were also reported. These findings support those of earlier descriptions of FAVC (Gackle, 2019; Huff-Gackle, 1985; Monks, 2003; Phillips et al, 2012; Williams et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…In males, the voice "break" is one of the hallmark characteristics of puberty. These physical mutations result in uncertainty and inconsistency in voice use, especially for those who consider themselves singers (Lauchsinger et al, 1965;Phillips et al, 2012). Although the female adolescent voice has received comparatively minimal attention from voice researchers, a few important studies have shown not only the validity of female adolescent voice change (FAVC) research, but also its importance in developing effective singing-voice-pedagogy practices.…”
mentioning
confidence: 99%